2012
DOI: 10.1007/s13142-012-0170-3
|View full text |Cite
|
Sign up to set email alerts
|

Charting a course for collaboration: a multiteam perspective

Abstract: The translation of medical research from bench-to-bedside often requires integrated input from multiple expert teams. These collectives can best be understood through the lens of multiteam systems theory. Team charters are a practical tool thought to facilitate team performance through the creation of explicit shared norms for behavior. We extend the current literature on team charters to the multiteam context and make three practical recommendations for multiteam charter content that could facilitate effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 44 publications
(59 reference statements)
1
26
0
Order By: Relevance
“…MTSs are defined as two or more teams that work interdependently towards at least one common goal 49. Initial work has begun to examine the leadership competencies that matter most in these contexts and to test interventions to cultivate them 50 51. However, further development and evaluation of team-training interventions targeting MTSs within the healthcare context are needed.…”
Section: Resultsmentioning
confidence: 99%
“…MTSs are defined as two or more teams that work interdependently towards at least one common goal 49. Initial work has begun to examine the leadership competencies that matter most in these contexts and to test interventions to cultivate them 50 51. However, further development and evaluation of team-training interventions targeting MTSs within the healthcare context are needed.…”
Section: Resultsmentioning
confidence: 99%
“…tools for assessing potential team members' readiness for collaboration , a toolkit of advice on team science (Vogel et al, 2013), scales for measuring collaboration and integration (Mâsse et al, 2008), team charters (Asencio et al, 2012) and a 'Collaboration Success Wizard' (Bietz et al, 2012).…”
Section: Theory Development: Organizational Discontinuities and The Pmentioning
confidence: 99%
“…Research on team science has suggested the need for teams to explicitly plan for their collaboration (e.g. Asencio et al, 2012), so this suggestion provides a specific focus for the planning. Recognition that there may be communication challenges gives members an opportunity to address them proactively.…”
Section: Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…To facilitate the smooth functioning of such a complex system, Asencio and colleagues [17] demonstrate the value of team charters. The team charter offers a practical tool to externalize and make explicit shared norms for behavior.…”
Section: Team Science Toolsmentioning
confidence: 99%